Compulsory Interventions in Severe and Persistent Mental Illness: A Survey on Attitudes Among Psychiatrists in Switzerland - Stoll, Julia; Hodel, Martina A.; Riese, Florian; Irwin, Scott A.; Hoff, Paul; Biller-Andorno, Nikola; Trachsel, Manuel (Frontiers in Psychiatry, 2021)
Background: Some psychiatric patients develop severe and persistent mental illness (SPMI), which, for a variety of reasons, can be therapy-refractory. Sometimes, treatment is not considered helpful by the patients themselves and does not improve their subjective quality of life. Furthermore, many SPMI patients experience compulsory interventions such as seclusion, restraint, or treatment against their will, which can cause harm. Methods: In a cross-sectional survey of 1311 German-speaking psychiatrists in Switzerland, participants were asked about the care of SPMI patients in general, and about their attitudes with regard to compulsory interventions in particular, using three case vignettes of patients with severe and persistent anorexia nervosa, schizophrenia and depression. Results: Out of 1311 contacted psychiatrists, 457 (34.9%) returned the completed survey. In general, 91.0% found it important or very important to respect SPMI patients’ autonomy in decision making. However, based on three different clinical case vignettes, 36.8% of psychiatrists would act against the wishes of the patient with severe and persistent schizophrenia, 34.1% against the wishes of the patient with severe and persistent depression, and 21.1% against the wishes of the patient with severe and persistent anorexia nervosa, although all patients were stated to have preserved decision-making capacity. With regard to the case vignettes, 41.1% considered compulsory interventions leading to a temporary reduction of quality of life acceptable in the patient with severe and persistent schizophrenia, 39.4% in the patient with severe and persistent depression, and 25.6% in the patient with severe and persistent anorexia nervosa, although it was stated in all three case vignettes that two independent experts ascribed the patients decision-making capacity regarding their illness and further treatment. Conclusions: Many psychiatrists in our sample found themselves in an ethical dilemma between autonomy and the provision of medical care. While most respondents respect the autonomy of SPMI patients, many saw the need to perform compulsory interventions even though it was clearly and prominently stated that two independent psychiatrists had ascribed the patients in the case vignettes decision-making capacity. Further examination of these conflicting views is warranted, perhaps along with the development of guidelines for such situations.